Parental metabolic syndrome and elevated liver transaminases are risk factors for offspring, even in children and adolescents with a normal body mass index - Song, Kyungchul; Yang, Juyeon; Lee, Hye Sun; Oh, Jun Suk; Kim, Sujin; Lee, Myeongseob; Suh, Junghwan; Kwon, Ahreum; Kim, Ho-Seong; Chae, Hyun Wook (Frontiers in Nutrition, 2023)
Introduction: The parent–child correlation in metabolic syndrome (MetS) and elevated transaminases is sparsely researched. We assessed the correlation of parental MetS and elevated transaminase status with these conditions in their children. Methods: Data of 4,167 youths aged 10–18 years were analyzed in a population-based survey, and the parental characteristics were stratified by the presence or absence of MetS or alanine aminotransferase (ALT) elevation in their children. The prevalence of these conditions in children was analyzed according to their parents' status. Logistic regression analyses were performed with MetS and ALT elevation in youth as the dependent variables. Results: The proportions of MetS and ALT elevation were higher in parents of children with MetS and ALT elevation than in those without, even among youths without obesity. In logistic regression analyses, age, body mass index–standard deviation score (BMI–SDS), and ALT elevation were positively associated with MetS, whereas age, male sex, BMI–SDS, protein intake, and MetS were positively associated with ALT elevation. Higher protein intake was related to ALT elevation, whereas metabolic components and nutritional factors were closely related in parents and their children. Odds ratios (OR) of ALT elevation for MetS was 8.96 even after adjusting nutritional factors in the children. The OR was higher for ALT elevation in the children of parents with MetS and ALT elevation compared to those without. ORs for MetS and ALT elevation in the children of parents with MetS were higher than those of children of parents without MetS, even after adjusting for nutritional intake. ORs for ALT elevation were higher in the children of parents with ALT elevation than those without, even after adjusting for nutritional intake and BMI of parents as well as the nutritional intake, age, sex, and BMI–SDS of the children. Conclusion: MetS and elevated liver transaminase statuses in children were associated with those of their parents even after adjusting for nutritional factors, and the relationships were more prominent in the youth without obesity.